Polymeric Approach to Adjuvant System in Antibody Production against Leishmaniasis Based on Hybridoma Technology - Asli Pinar Zorba Yildiz; Gulnaz Yildirim Koken; Emrah Sefik Abamor; Melahat Bagirova; Ozlem Ayse Tosyali; Tanil Kocagoz; Adil Allahverdiyev (Iranian Journal of Parasitology, 2022)
Background: Leishmaniasis is a zoonotic disease, which is one of the serious public health problems in the world. Nowadays, antibody production using hybridoma technology may be a correct approach in terms of sensitivity in the diagnosis of diseases such as leishmaniasis. The aim of this study was investigation of the effectiveness of different adjuvants on polyclonal antibody production against L. tropica based on hybridoma technique.